2021
DOI: 10.33963/kp.a2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Is cytisine contraindicated in smoking patients with coronary artery disease after percutaneous coronary intervention?

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.Is cytisine contraindicated in smoking patients with coronary artery disease after percutaneous coronary intervention?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Seven newly conducted RCTs [15][16][17][18][19][20][21] were identified that were not considered in any of the preceding rereviews [2,23,24,27]. Eleven trials [28][29][30][31][32][33][34][35][36][37] were excluded. The excluded studies are briefly described, with justification for each exclusion, in the Characteristics of Excluded Studies tables (Supporting information).…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…Seven newly conducted RCTs [15][16][17][18][19][20][21] were identified that were not considered in any of the preceding rereviews [2,23,24,27]. Eleven trials [28][29][30][31][32][33][34][35][36][37] were excluded. The excluded studies are briefly described, with justification for each exclusion, in the Characteristics of Excluded Studies tables (Supporting information).…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…Only 64 (26.5%) patients in the present study used any form of pharmacological smoking aid. We failed to find any correlation between drug use and effect in SC; but, as reported previously by our group, cytisine use may be effective only in patients who completed the treatment [28]. We did not measure e-cigarette usage which might be relevant in SC but also might carry harmful effects [29].…”
Section: Discussionmentioning
confidence: 63%
“…La seguridad de TSN se ha comprobado en multitud de estudios 41 , 42 . Un estudio prospectivo, no aleatorizado, realizado en 117 fumadores sometidos a una intervención coronaria percutánea 30 días antes del tratamiento con citisina concluyó que la citisina no incrementa los efectos adversos en estos pacientes 43 . Por otro lado, Prochaska y Hilton 44 realizaron un metaanálisis de 22 ensayos clínicos, doble ciego, controlados con placebo, para valorar el riesgo de eventos adversos cardiovasculares en pacientes tratados con vareniclina durante el tratamiento y después de 30 días de finalizar el mismo, donde no se observó un aumento de eventos cardiovasculares.…”
Section: ¿Se Puede Hacer Una Intervención En Tabaquismo En Cualquier ...unclassified